Factors Influencing the Satisfaction Level of Medical Tourist in Malaysia - Pang Hui Ting; R. Chandrashekar (Research in Management of Technology and Business, 2023)
Medical tourism refers to the act of traveling to other countries for medical treatment, dental care, and surgical care, etc. Malaysia is one of the world-famous medical destinations, including Brunei, the Philippines, Singapore and Thailand. The current problem statement is some other developing ASEAN countries such as Philippines and Nepal do not provide high-quality healthcare, sufficient resources and infrastructure so they do not have the chance to get medical services in their own countries. Therefore, this research is significant to study what are the factors influencing the satisfaction level of inbound tourist who visit to Malaysia for medical care. The Statistical Package for Social Sciences (SPSS) will be used to examine the data. During the whole research process, the researcher distributed questionnaire to 384 inbound ASEAN tourists in Kuala Lumpur, Malaysia, and 240 respondents agreed to participant in the research. The results show that all the variables (Cost, Quality, Facility, Service and Environment of medical care) are positively correlated to the satisfaction level of medical tourist.